Vitamin D, parathyroid hormone, serum calcium and phosphorus in patients with schizophrenia and major depression. (February 2013) - Jamilian, Hamidreza; Bagherzadeh, Kamran; Nazeri, Zeinab; Hassanijirdehi, Marzieh
Abstract Objective. Vitamin D deficiency has been associated with an increased risk of depression and schizophrenia. The aim was to compare serum levels of vitamin D, calcium, phosphorus and parathyroid hormone in schizophrenics, depressed patients and healthy subjects in an Iranian population. Methods. In a cross-sectional study, 100 patients with schizophrenia and 100 with major depression were enrolled. A questionnaire was filled by using medical records of patients. After that a serum sample was taken and levels of vitamin D, calcium, phosphorus and parathyroid hormone were assessed and then compared between the three groups. Results. Post-hoc analysis of Tukey showed that vitamin D level in healthy participants was significantly higher than depressed patients and schizophrenics while there was no significant difference between vitamin D level in depressed and schizophrenic patients. Conclusion. The findings suggest that vitamin D affects the brain independent of hormonal pathways which regulate serum level of calcium. Non-significant difference in the serum level of vitamin D between the schizophrenics and the depressed patients suggests that the independent effect of vitamin D in brain is a general effect and is not specialized to a specific region or pathway in the brain; however, differences between psychiatric and non-psychiatric patients might be resulted from differences in psychosocial backgrounds.